Characterization of an exopolysaccharide produced by Lactobacillus plantarum HM47 isolated from human breast milk. (October 2018) - Nambiar, Reshma B; Sellamuthu, Periyar Selvam; Perumal, Anand Babu; Sadiku, Emmanuel Rotimi; Phiri, Goitse; Jayaramudu, J.
Graphical abstract: Highlights: Exopolysaccharide (EPS) producing L. plantarum HM47 was isolated from human breast milk. EPS showed higher viscosity at lower temperature, acidic pH and also in skim milk. The heteropolysaccharide EPS included glucose and galactose. EPS exhibited high thermal stability. Abstract: In the present study, exopolysaccharide (EPS) secreted by Lactobacillus plantarum HM47, was purified and characterized. The structural characterization of EPS revealed that it was a polymer of glucose, and galactose in the ratio of 0.5:1.4. The FTIR spectroscopy showed the prevalence of carboxyl and hydroxyl groups. 1 H NMR and 13 C NMR spectra analysis showed the presence of β-d -glucose and β-d -galactose. The EDX analysis inferred the presence of C, O, P, Na, Cl and S. SEM micrographs exhibited a highly porous structure that showed plasticized film characteristics. Thermal analysis inferred high thermal stability of EPS with the maximum degradation temperature (Td ) of 273.6 °C. Thus, the higher thermal stability and the physical characteristics of EPS from L. plantarum HM47 makes it an ideal material for the food industry.